SIGNIFICANCE OF ONTIC DUTY - Moń, Ryszard (Studia Philosophiae Christianae, 2020)
What are the relationships between value and duty? Which ontic status has a duty and why? This article aims at clarifying these concepts. It is indicated that in Kant’s writings, we come across texts that enable a slightly different interpretation of his philosophy. And so: the ma%er of good will is the goals themselves; good will must act according to the maxim that the members of the kingdom of goals follow. And this is a moral good since the highest principle of morality is the desire for autonomy of will. Thus, the form of universal legislation is a community of autonomous beings in which the humanity of each of them is realized. In such a community, the a priori content – the content of an ethical reality – is created. It can be said that relationships between people are various forms of ontic status of a duty.